2021
DOI: 10.3390/toxins13010024
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Aflatoxin B1 Sequestration by Yeast Cell Wall Extract and Hydrated Sodium Calcium Aluminosilicate Evaluated Using a Multimodal In-Vitro and Ex-Vivo Methodology

Abstract: In this work, adsorption of the carcinogenic mycotoxin aflatoxin B1 (AFB1) by two sequestrants—a yeast cell wall-based adsorbent (YCW) and a hydrated sodium calcium aluminosilicate (HSCAS)—was studied across four laboratory models: (1) an in vitro model from a reference method was employed to quantify the sorption capabilities of both sequestrants under buffer conditions at two pH values using liquid chromatography with fluorescence detection (LC-FLD); (2) in a second in vitro model, the influence of the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…Our results revealed that the two adsorbents exhibited a highly significant propensity for maintaining higher toxin concentrations in the digestive compartment at both tested time points. This finding confirmed the ability of the adsorbents to limit the intestinal bioavailability of AFB1, leading to a decrease in the absorption of 3 H-AFB1 through the intestine, which further confirmed the previously studied direct [25,46] and indirect mitigation effects observed in various animal species [31,32,44].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our results revealed that the two adsorbents exhibited a highly significant propensity for maintaining higher toxin concentrations in the digestive compartment at both tested time points. This finding confirmed the ability of the adsorbents to limit the intestinal bioavailability of AFB1, leading to a decrease in the absorption of 3 H-AFB1 through the intestine, which further confirmed the previously studied direct [25,46] and indirect mitigation effects observed in various animal species [31,32,44].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we were able to highlight both binders' capacity in significantly decreasing the plasma concentration of AFB1 in rats subjected to dietary AFB1 exposure (Figure 5a). We can draw a parallel between this finding and recent findings obtained employing a bicameral Ussing chamber system in an ex vivo setup, in which a reduction in the transfer of AFB1 through the rat intestinal explants led to a decrease in the concentration of AFB1 in the serosal compartment following the use of both YCW and HSCAS [25]. Interestingly, when comparing the 5-and 10-h post-feeding timepoints of the present study, further accumulation of AFB1 could be observed over time, which was effectively prevented by both YCW and HSCAS.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations